Digestibility, Milk Yields, and Milk Quality of Ettawa Crossbred Goats Fed Coleus amboinicus L. Leaf Extract - M. Afdal; D. Darlis; A. Adriani (Tropical Animal Science Journal, 2021)
Coleus amboinicus L. leaf (CAL) could reduce the rate of amino acid deamination and protein degradation within the rumen. This phenomenon would hopefully increase the amount of protein that passes through the rumen to the abomasum. Therefore, it might improve the digestibility of the ration and then influence the milk yield and quality. The objective of this experiment was to evaluate the effect of extracted CAL within the ration on the ration digestibility, milk yield, and milk quality of Ettawa crossbred (EC) goats. This study used sixteen EC with an average weight of 32.25 ± 3.31 kg and aged 1.5–2.5 years. Experimental goats were fed diets with different CAL extracts: P0, 0% (control); P1, 2% powdered CAL; P2, 2% ethanol-extracted CAL; and P3, 2% water-extracted CAL. The experiment was conducted in a randomized block design with four replication blocks. All variables were statistically analyzed with ANOVA and significances were followed by Duncan’s test. P3 treatment significantly (p<0.05) increased milk yield and milk quality in comparison with control. Unlike the other treatments, P3 treatment was water-extracted CAL that could affect these variables. P3 treatment showed the best result among the four treatments. In conclusion, P3 treatment, the supplementation of 2% water-extracted CAL within the ration, could improve the milk yield up to 30.24% in comparison with the control ration and also improve milk composition, such as milk protein (4.47%), milk casein (3.99%), milk fat (3.85%), and solid nonfat (SNF) (6.53%). The supplementation of water-extracted CAL within ration could improve the milk yield and milk quality of EC.